The Role of Oil Palm and Rubber Industry toward Regional Economic in West Kalimantan-Indonesia - Arman, Arman; Saefuddin, Asep; Pradina, Fathia Anggriani (Bina Nusantara University, 2017)
The study aimed to assess the role of palm oil and rubber toward the economy in West Kalimantan. Another aim was to develop oil palm and rubber industry to strengthen the economy of West Kalimantan. The method used in this research was the analysis of Input-Output. The main data was the Input-Output (IO) data in 2011 from the Central Bureau of Statistics (BPS), which consists of 54 sectors. The results show that the industrial output of palm oil and rubber, as well as oil palm and rubber, is still low. Weak innovation and technology lead to the low output and role of these two sectors to the economy of West Kalimantan. Another obstacle that leads to the economy of rubber and palm oil industries under the standard is the lack of motivation research, infrastructure, and connectivity.